AB0381 Long-Term Clinical Effectiveness of Adalimumab, Etanercept, and Infliximab in Rheumatoid Arthritis (RA): an Observational Study from Italian Register, Gisea. (10th June 2014) - Iannone, F.; Marchesoni, A.; Sarzi-Puttini, P.; Gorla, R.; Govoni, M.; Carletto, A.; Ferraccioli, G.; Ferri, C.; Punzi, L.; Salaffi, F.; Foti, R.; Lapadula, G.
Abstract : Background: In routine care, patients with active RA usually undergo treatment with TNF inhibitors. The choice of the durg is empirical and there are not established predictors of long-term clinical outcomes Objectives: To evaluate 4 years effectiveness of adalimumab (ADA), etanercept (ETN), and infliximab (IFX), in patients with active RA from the GISEA (Gruppo Italiano Studio Early Arthritis) Methods: RA patients starting a first ever TNF inhibitor in years 2003-2004 with complete clinical data for at least 2 years were included in this study. The analysis was extended up to 4 years by using the LOCF analysis to account for missing data. The percentage of patients achieving the EULAR good response (change of DAS28 from baseline ≥1.2), or disease remission (defined as DAS28 <2.6), or improvement of function ability (change of HAQ from baseline >0.5) was compared between groups using χ 2 test. Logistic multiple regression analysis was used to assess baseline predictors of DAS28-based disease remission or EULAR good response. Baseline variables gender, age at the diagnosis, age at the beginning of therapy, disease duration, HAQ, DAS28, number of previous DMARDs, anti-TNF-a drug were considered in the regression model Results: We analysed data records from 352 patients (female 85%, median age 45.8 years, median duration of disease 6.9 years, median DAS28 5.95, median HAQ 1.25) with RA starting adalimumab (ABA) (nr 136), or etanercept (ETN) (nr 121) or infliximab (IFX) (nr 95). DAS28 was similar between treatment groups as well as disease duration or autoimmunity status (RF/ACPA), but HAQ was significantly higher in IFX group (p=0.001). Instead, age at the diagnosis and age at the beginning of therapy were significantly higher in ADA group (p=0.03 and p=0.02, respectively). At 2 years, the percentage of patients discontinuing the therapy was 21% for ADA, 42% for ETN, and 36% for IFX. At 2 years, the percentage of patients achieving EULAR good response or DAS28-based disease remission or HAQ improvement >0.5 was 56%, 36%, and 71% for ADA, 50%, 32% and 59% for ETN, and 59%, 30% and 71% for IFX, respectively, and the difference was no statistically significant. According to LOCF analysis, also at 4 years, clinical response rates were similar (EULAR good response, DAS28-based disease remission, HAQ improvement >0.5: 57%, 40%, and 55% for ADA, 54%, 38% and 61% for ETN, and 43%, 30% and 52% for IFX, respectively). Multiple regression analysis showed that gender female was an independent negative predictor of good EULAR response at 1 year (OR: 0.46, 95% IC:0.24-0.88), and DAS28-based remission at 2 years (OR: 0.50, 95% IC:0.26-0.98), as well as the age at the beginning of biologic therapy (good EULAR response at 1 year OR: 0.97, 95% IC:0.95-0.98, and DAS28-based remission at 2 years OR: 0.93, 95% IC:0.90-0.97). Instead, the type of TNF inhibitor did not correlate with the clinical response Conclusions: In this 4-year survey, ADA, ETN, and IFX showed a similar effectiveness and female patients had more odds to discontinue the therapy Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5721